Bedforms of Thwaites Glacier, West Antarctica: Character and Origin - Alley, RB; Holschuh, N; MacAyeal, DR; Parizek, BR; Zoet, L; Riverman, K; Muto, A; Christianson, K; Clyne, E; Anandakrishnan, S; Stevens, N; Collaboration, GHOST (Journal of Geophysical Research: Earth Surface, 2021)
Bedforms of Thwaites Glacier, West Antarctica both record and affect ice flow, as shown by geophysical data and simple models. Thwaites Glacier flows across the tectonic fabric of the West Antarctic rift system with its bedrock highs and sedimentary basins. Swath radar and seismic surveys of the glacier bed have revealed soft-sediment flutes 100 m or more high extending 15 km or more across basins downglacier from bedrock highs. Flutes end at prominent hard-bedded moats on stoss sides of the next topographic highs. We use simple models to show that ice flow against topography increases pressure between ice and till upglacier along the bed over a distance that scales with the topography. In this basal zone of high pressure, ice-contact water would be excluded, thus increasing basal drag by increasing ice-till coupling and till flux, removing till to allow bedrock erosion that creates moats. Till carried across highlands would then be deposited in lee-side positions forming bedforms that prograde downglacier over time, and that remain soft on top through feedbacks that match till-deformational fluxes from well upglacier of the topography. The bedforms of the part of Thwaites surveyed here are prominent because ice flow has persisted over a long time on this geological setting, not because ice flow is anomalous. Bedform development likely has caused evolution of ice flow over time as till and lubricating water were redistributed, moats were eroded and bedforms grew.